Love & basketball - Blanchard, Terence 1962- (<<The>> Criterion Collection, 2021)
"Monica and Quincy love and play basketball together through many life challenges from childhood to adulthood." [imdb.com]
Original: USA 2000
director-approved two-DVD special edition features: new 4K digital restoration, supervised by director Gina Prince-Bythewood, featuring additional footage cut from the original release ; two audio commentaries from 2000: one featuring Prince-Bythewood and actor Sanaa Lathan and the other featuring Prince-Bythewood, editor Terilyn A. Shropshire, and composer Terence Blanchard ; new making-of documentary featuring Prince-Bythewood, Lathan, actors Omar Epps and Alfre Woodward, producer and writer Reggie Rock Bythewood, and basketball advisor Colleen Matsuhara ; "Editing 'Love & basketball'," a new program featuring Prince-Bythewood, and Shropshire ; new conversation among Prince-Bythewood, WNBA legend and Hall of Famer Sheryl Swoopes, and writer-producer-actor Lena Waithe ; deleted scenes with optional audio commentary by Prince-Bythewood and Shropshire ; audition tape excerpts ; two short films by Prince-Bythewood: her UCLA thesis film, "Stitches" (1991) and "Progress" (1997), with a new introduction by the director ; trailer ; plus: an essay by author Roxane Gay
Bildformat 1.85:1
Keywords: Film; DVD-Video